Silicon and soil microorganisms improve rhizospheric soil health with bacterial community, plant growth, performance and yield. (31st December 2022) - Verma, Krishan K.; Song, Xiu-Peng; Li, Dong-Mei; Singh, Munna; Wu, Jian-Ming; Singh, Rajesh Kumar; Sharma, Anjney; Zhang, Bao-Qing; Li, Yang-Rui
ABSTRACT: The interaction of silicon and soil microorganisms stimulates crop enhancement to ensure sustainable agriculture. Silicon may potentially increase nutrient availability in rhizosphere with improved plants' growth, development as it does not produce phytotoxicity. The rhizospheric microbiome accommodates a variety of microbial species that live in a small area of soil directly associated with the hidden half plants' system. Plant growth-promoting rhizobacteria (PGPR) play a major role in plant development in response to adverse climatic conditions. PGPRs may enhance the growth, quality, productivity in variety of crops, and mitigate abiotic stresses by reprogramming stress-induced physiological variations in plants via different mechanisms, such as synthesis of indole-3-acetic acid, 1-aminocyclopropane-1-carboxylate deaminase, exopolysaccharides, volatile organic compounds, atmospheric nitrogen fixation, and phosphate solubilization. Our article eye upon interactions of silicon and plant microbes which seems to be an opportunity for sustainable agriculture for series of crops and cropping systems in years to come, essential to safeguard the food security for masses.